Diagnosis and therapy of gestational diabetes - Maria Magdalena Salmanowicz; Patrycja Nowicka; Bolesław Banach; Arnold Kukowka (Polish Pharmaceutical Society, 2022)
In Poland, 3 to 12% of pregnant women suffer from gestational diabetes. Untreated diabetes is associated with a number of complications for both the fetus and the mother. This article reviews current standards in the diagnosis and treatment of Gestational Diabetes Mellitus (GDM). GDM is asymptomatic, which is why screening performed as soon as pregnancy is established and between 24 and 28 weeks of gestation is so important. At the first visit, risk factors for hyperglycemia in pregnancy should be assessed, as pregnant women at risk should have a 75 g oral glucose tolerance test (OGTT) performed at the first visit. Screening and diagnostic tests for GDM are lengthy and have low reproducibility. This has prompted work to identify biomarkers that can replace the OGTT and allow the introduction of universal screening tests with high sensitivity and specificity in detecting pregnant women at risk for GDM. One such biomarker is CD59 glycoprotein. Nutritional therapy is the cornerstone of treatment for women with GDM. It should be conducted taking into account changes in eating habits, lifestyle, introduction of physical activity and control of weight gain. It is essential to educate the patient about the diabetic diet, including the importance of glycemic index, glycemic load and factors modifying its value. The low-carbohydrate preload strategy, which involves eating carbohydrates last, after proteins and fats, deserves attention. As many as 70-85% of women with GDM achieve normal blood glucose levels after lifestyle changes and do not require additional intervention, but the remaining patients need more intensive treatment.In Poland, if behavioral therapy is not effective, s.c. insulin therapy should be implemented. Oral insulin delivery is of interest to many researchers, but the work is still in progress. Overseas, oral antidiabetic drugs are also used in the treatment of women with GDM and they are metformin and gliburide. However, there are many doubts about both the efficacy and safety of these preparations.